Exploring the Management of Virtual Learning Environments: Insights from Senior High School Practices - Purnomo, Eko Nurhaji; Abdur ROfik (RAHMATAN LIL ALAMIN: Journal of Peace Education and Islamic Studies, 2025)
Abstract: This study examines the strategic management of Virtual Learning Environments (VLEs) in upper secondary schools through an interpretive qualitative approach. Data were collected via semi-structured interviews with school principals, teachers, and IT staff, and analyzed using NVivo software. The analysis revealed six core themes: visionary leadership, integrated development strategies, the creation of digital learning resources, pedagogical and classroom adaptation, supervisory mechanisms, and technical challenges. Visionary leadership within schools emerged as a critical driver of digital innovation and the cultivation of future-ready skills among both students and educators. The findings underscore the importance of designing VLEs that are responsive to the dynamic pedagogical, technological, and administrative demands of contemporary education systems. This study highlights the need for school leaders to facilitate digital transformation through capacity building and the promotion of a collaborative digital culture. Moreover, the integration of adaptive instructional strategies and real-time monitoring mechanisms within Learning Management Systems (LMS) is shown to significantly enhance instructional quality and learner engagement. The study offers practical implications for educational leaders, policymakers, and practitioners by providing a comprehensive empirical framework for the sustainable development of VLEs that promote equity, innovation, and lifelong learning in the digital era.